Comparison of quality of life in patients operated for knee surgery via conventional method and arthroscopy: An original research - Deepak Rohella; A P J Swathy; Rajunaik Ajmeera; Prajnyananda Das; Rahul V C Tiwari; Heena Dixit Tiwari (Wolters Kluwer Medknow Publications, 2023)
Introduction: To assess physical activity and knee function, the two methods of conventional supervised exercise and the arthroscopic partial meniscectomy trailed by exercise were evaluated after a nontraumatic meniscal (medial) tear that was confirmed on magnetic resonance imaging (MRI). Materials and Methods: One hundred adult subjects were assessed for the current prospective research. The pain in the knee was assessed using the Knee Injury and Osteoarthritis Outcome Score (KOOS), Lysholm Knee Scoring Scale (LKSS), Tegner Activity Scale (TAS), and Visual Analogue Scale (VAS). All the parameters were compared at the start of the study and 2 and 6 months after the intervention. All the data were compared using the analysis of variance (ANOVA) with P < 0.05 considered as significant. Results: According to the outcome scores, exercising by itself did not result in a larger improvement than an arthroscopic partial medial meniscectomy. There was a significant reduction in discomfort, improved function, and satisfaction for subjects in the two groups (P < 0.0001). After six months, 40% of the subjects reported that the activity levels were similar to the incidence of the injury. Conclusion: The quality of life was reported to be comparable in the arthroscopy subjects and the conventional group subjects. Hence, arthroscopy can be delayed for the meniscal tear in the adult subjects who are best managed by the conservatively managed.